Cocoa beans improve mitochondrial biogenesis via PPARγ/PGC1α dependent signalling pathway in MPP+ intoxicated human neuroblastoma cells (SH-SY5Y). (2nd June 2020) - Chidambaram, Saravana Babu; Bhat, Abid; Ray, Bipul; Sugumar, Mani; Muthukumar, Serva Peddha; Manivasagam, Thamilarasan; Justin Thenmozhi, Arokiasamy; Essa, Musthafa Mohamed; Guillemin, Gilles J.; Sakharkar, Meena Kishore
Abstract : Polyphenols are shown to protect from or delay the progression of chronic neurodegenerative diseases. Mitochondrial dysfunction plays a key role in the pathogenesis of Parkinson's disease (PD). This study was aims to gain insight into the role of ahydroalcoholic extract of cocoa (standardised for epicatechin content) on mitochondrial biogenesis in MPP + intoxicated human neuroblastoma cells (SHSY5Y). The effects of cocoa on PPARγ, PGC1α, Nrf2 and TFAM protein expression and mitochondrial membrane potential were evaluated. A pre-exposure to cocoa extract decreased reactive oxygen species formation and restored mitochondrial membrane potential. The cocoa extract was found to up-regulate the expression of PPARγ and the downstream signalling proteins PGC1α, Nrf2 and TFAM. It increased the expression of the anti-apoptotic protein BCl2 and increased superoxide dismutase activity. Further, the cocoa extract down-regulated the expression of mitochondria fission 1 (Fis1) and up-regulated the expression of mitochondria fusion 2 (Mfn2) proteins, suggesting an improvement in mitochondrial functions in MPP + intoxicated cells upon treatment with cocoa. Interestingly, cocoa up-regulates the expression of tyrosine hydroxylase, the rate limiting enzyme in dopamine synthesis. No change in the expression of PPARγ on treatment with cocoa extract was observed when the cells were pre-treated with PPARγ antagonist GW9662. This data suggests that cocoa mediates mitochondrial biogenesis via a PPARγ/PGC1α dependent signalling pathway and also has the ability to improve dopaminergic functions by increasing tyrosine hydroxylase expression. Based on our data, we propose that a cocoa bean extract and products thereof could be used as potential nutritional supplements for neuroprotection in PD.